Exploring the Future of Ayush Research: Advancing Homeopathy through Scientific Integration and Innovation” (Homoeopathy for All, 2025)
The AYUSH system, which  encompasses Ayurveda, Yoga,  Unani, Siddha, and Homeopathy,  represents a rich legacy of  traditional healing that continues  to shape healthcare in India and  beyond. Among these, Homeopathy  has gained significant global  recognition for its holistic, patient centered approach to treatment.  Strengthening research in AYUSH,  particularly in Homeopathy, requires  integrating traditional wisdom with  modern scientific methodologies to  establish efficacy, ensure safety, and  foster wider acceptance.
Keywords: traditional; healing